2019
DOI: 10.1016/j.actamat.2019.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A correlative four-dimensional study of phase-separation at the subnanoscale to nanoscale of a Ni Al alloy

Abstract: The temporal evolution of ordered γ'(L12)-precipitates precipitating in a disordered γ(f.c.c.) matrix is studied in extensive detail for a Al at.% alloy aged at 823 K (550 o C), for times ranging from 0.08 to 4096 h. Three-dimensional atom-probe tomography (3-D APT) results are compared to monovacancy-mediated lattice-kinetic Monte Carlo (LKMC1) simulations on a rigid lattice, which include monovacancy-solute binding energies through 4 th nearest-neighbor distances, for the same mean composition and aging tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 159 publications
(341 reference statements)
0
16
0
Order By: Relevance
“…and the value reported by Wendt and Haasen (0.005) is quite inconsistent with the solubility limit at 823 K (X ce = 0.1074). The investigation of Plotnikov et al [22] bears some similarities to that of Wendt and Haasen in that the aging temperature, 823 K, was the same and ATP figured prominently in the research. The main differences were the smaller alloy concentration, 12.50 at.…”
Section: A the Kinetics Of Solute Depletionmentioning
confidence: 57%
See 4 more Smart Citations
“…and the value reported by Wendt and Haasen (0.005) is quite inconsistent with the solubility limit at 823 K (X ce = 0.1074). The investigation of Plotnikov et al [22] bears some similarities to that of Wendt and Haasen in that the aging temperature, 823 K, was the same and ATP figured prominently in the research. The main differences were the smaller alloy concentration, 12.50 at.…”
Section: A the Kinetics Of Solute Depletionmentioning
confidence: 57%
“…Using their data to calculateD c andD c 0 at the equilibrium compositions of both phases (see Appendix A), and substituting the results into Eq. [18], leads to the temperature dependence of D c =D I displayed in Figure 1 The interface width, d, was estimated from the limited sources of available experimental data, i.e., the composition profiles across c/c¢ interfaces published by Plotnikov et al [21,22] and a value of d reported by Forghani et al [23] Details of the analyses used to extract the data from figures published by Plotnikov et al are provided in Appendix B; the analyses assume that the concentration profile across an interface is best described by a sigmoid function. [24] The results, based on limited data, indicate that d increases with increasing temperature.…”
Section: The Tidc-lsw Transition Radius and Interface Widthmentioning
confidence: 99%
See 3 more Smart Citations